Evaluasi Program Respon Cepat Pencegahan Pencurian Diatas Kapal Diarea Labuh Jangkar Tanjung Priok Jakarta - Hendarto Hendarto; Siti Aisyah; Effendi Wahyono (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The sea serves as a vital artery for Indonesia’s national economy; however, the high intensity of maritime activities at major ports such as Tanjung Priok, Jakarta, makes the area vulnerable to incidents of theft on board ships. As a preventive effort, the Directorate of Marine Police of the Indonesian National Police launched the Quick Response Program for the Prevention of Theft on Board Ships to enhance maritime security in anchorage areas. This study aims to evaluate the effectiveness of the program’s implementation using the CIPP evaluation model (Context, Input, Process, Product). The research employed a qualitative approach, with data collected through in-depth interviews, participatory observation, and documentation studies involving Polairud personnel, port authorities, ship operators, and maritime service users. The results indicate that, contextually, the program is highly relevant to national maritime security needs; however, its planning remains normative and lacks a comprehensive situational analysis. In the input dimension, limitations in human resources, patrol fleet capacity, and insufficient technical training for approximately 40% of personnel are identified as major constraints. The process dimension reveals weak interagency coordination due to the absence of integrated Standard Operating Procedures (SOPs), which extend the average response time from the ideal 5–10 minutes to 20–30 minutes. Meanwhile, the product dimension shows that although the number of theft cases decreased from 97 in 2022 to 76 in 2023, the program’s long-term effectiveness remains limited due to the absence of a sustainable evaluation and feedback mechanism.